Near- and mid-infrared intersubband absorption in top-down GaN/AlN nano- and micro-pillars. (30th November 2018) - Lähnemann, Jonas; Browne, David A; Ajay, Akhil; Jeannin, Mathieu; Vasanelli, Angela; Thomassin, Jean-Luc; Bellet-Amalric, Edith; Monroy, Eva
Abstract: We present a systematic study of top-down processed GaN/AlN heterostructures for intersubband optoelectronic applications. Samples containing quantum well superlattices that display either near- or mid-infrared intersubband absorption were etched into nano- and micro-pillar arrays in an inductively coupled plasma. We investigate the influence of this process on the structure and strain-state, on the interband emission and on the intersubband absorption. Notably, for pillar spacings significantly smaller (≤1/3) than the intersubband wavelength, the magnitude of the intersubband absorption is not reduced even when 90% of the material is etched away and a similar linewidth is obtained. The same holds for the interband emission. In contrast, for pillar spacings on the order of the intersubband absorption wavelength, the intersubband absorption is masked by refraction effects and photonic crystal modes. The presented results are a first step towards micro- and nano-structured group-III nitride devices relying on intersubband transitions.